Phenomenology in adaptation planning : an empirical study of flood-affected people in Kampung Muara Baru Jakarta /: an empirical study of flood-affected people in Kampung Muara Baru Jakarta. ([2018]) - Simarmata, Hendricus Andy
No abstract available